Analysis of Reinforcing Factor with Involvement of Informal Sector Workers in Occupational Health Post (Pos UKK) - Muhammad Dyas Husnan Khair; Ayun Sriatmi; Bina Kurniawan (Journal of Public Health for Tropical and Coastal Region, 2018)
Background: Occupational Health Post (Pos UKK) is a program aims to improve occupational health and productivity of informal sector workers in Indonesia through promotive, preventive, simple curative and rehabilitative care with the principle of Community Based Health Efforts (UKBM). The number of Pos UKK registered in Semarang City Health Office is 30 units. The results of the preliminary study illustrate different situations because there were only 6 Pos UKK. Among those, only 2 were active (6.7%) from the registered Pos UKK. It’s alleged that inactivity of Pos UKK due to low support from various parties and impacted on low sustainability of the program. This study aims to analyze the reinforcing factor with the involvement of informal sector workers in Pos UKK in Semarang City.Methods : Quantitative study with cross sectional approach. Population were 146 workers and selected sample were 70 workers. Independent variables include co-worker support, business owner support and Community Health Centre (Puskesmas) support and dependent variable is involvement of informal sector workers in Pos UKK.Results : Majority of informal sector workers involvement in Pos UKK were low (51,43%). Co-worker and business owners support was good but Puskesmas support as guide was not. Statistically, co-worker support (p = 0,000, OR = 30.8), business owner support (p <0.001, OR = 10.6) and Puskesmas support (p <0.001, OR = 13.5) proved to have a significant relationship. Conclusion:This study showed that reinforcing factors have significant relationship in increasing involvement of informal sector workers in Pos UKK to ensure program sustainability. Puskesmas is expected to provide continuing assistance and socialization about the benefits of Pos UKK to informal sector workers.